Advances in the Management of Cancer by Natural Products: An Overview - Gupta, Rajiv (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Drugs derived from natural origin are often derived from medicinal plants. The extract thus obtained may be from a single plant or polyherbal, that is, a combination of botanical extracts that are assumed to have additive or synergistic effects, although some antagonistic action has also been reported. It is documented that the majority of terrestrial and marine plants have still not been fully explored regarding their prophylactic or therapeutic properties. As per the guidelines of the Committee for the Purpose of Control and Supervision of Experiments on Animals and Institutional Animal Ethics Committee, in the absence of preliminary toxicity or activity data, the direct use of experimental animals in sacrificial/painful models is also not fully justified. A cell line is defined as a permanently established cell culture that will proliferate indefinitely when given an appropriate fresh medium and space. Cell lines consist of cells with a uniform genetic makeup because they developed from a single cell and their subsequent growth occurs in a favorable artificial media or environment. Cell lines differ from cell strains in that they become immortalized. According to the World Health Organization, developing countries like India need to fully explore the potential of their traditional drugs in the management of various diseases, either in prophylaxis or therapeutics, to become economically self-reliant. Cancer is reported as the second primary cause of death globally; nearly one in six deaths is caused by cancer disease. Applying cancer models on experimental animals leads to a painful death. It was, therefore, thought worthwhile to compile and critically analyze the major published studies, where an herbal extract or drug of natural origin has been tried on cell lines, particularly on cancer cells, as an alternative to experimental animals.